Pemberian Tapid Sponge terhadap Penurunan Suhu Tubuh pada Anak Toodler (1-3 Tahun) - Heni Heni; Arni Wianti; Idris Handriana; Sinta Oktaviana (Jurnal Keperawatan Silampari, 2023)
This study aims to determine the effect of tapid sponge administration on decreasing body temperature in toddlers (1-3 years) in the Melati Room at Majalengka Hospital in 2022. This study used a quantitative approach with a quasi-experimental method. The study's results showed that 27 children in the Melati Room at Majalengka Hospital experienced a decrease in body temperature, and one person experienced an increase in body temperature. The Wilcoxon signed ranks test results obtained a p-value of 0.000 (<0.05). In conclusion, tapid sponge administration has an effect on decreasing body temperature in toddlers (1-3 years) in the Melati Room of Majalengka Hospital in 2022. Keywords: Toddler Children, Body Temperature, Tapid Sponge